A whole ecosystem perspective of hypoxia and its drivers in a large temperate freshwater estuary - Shelby Brunner; Brice Grunert; Kim Weckerly; Pat Anderson; J. Val Klump (Limnology and Oceanography, 2026)
Hypoxic conditions have become increasingly common during the summer in the bottom waters of seasonally stratified inland and coastal waters. While ultimately driven by carbon and nutrient loading from the watershed and subsequent excessive algal production, the formation and duration of hypoxia are largely controlled by coupled physical‐biogeochemical processes. In this study of Green Bay, Lake Michigan, δ 2 H and δ 18 O isotopic tracers illustrate the conservative, estuarine‐like mixing pattern that dominates summertime stratification. Cold hypolimnetic waters originating from Lake Michigan in the northern end of the bay slowly propagate southward (~ 1 km per day) into the increasingly shallower southern bay beneath warmer Fox River and lower Green Bay surface waters, generating a highly stratified water column susceptible to the onset and persistence of hypoxia. As waters become shallower, the hypolimnion compresses and the role of benthic respiration increases, oxygen depletion develops more rapidly, and hypoxia becomes most prevalent. Measurements of sediment oxygen demand at 30 stations (mean = 8.2 mmol m −2 d −1 ) and calculations of apparent oxygen utilization rates within stratified bottom waters result in estimates of sediment oxygen consumption accounting for 14–87% of the total oxygen depletion in the hypolimnion from late July through early September. Residence times for dissolved oxygen in the hypoxic zone are on the order of weeks, making Green Bay sensitive to projections of prolonged stratification and potentially exacerbating hypoxia under a warming climate.